1981
DOI: 10.1002/bjs.1800681105
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide biliary scanning in acute pancreatitis

Abstract: Radionuclide biliary scanning with 99 TcVabelled HIDA was performed in 36 patients with acute pancreatitis within 3 days of admission. Twenty had a non-visualized gallbladder on scanning and all were subsequently shown by cholecystography (n = 16) and/or operation (n = 16) to have underlying gallstones; 5 of the 16 cholecystograms revealed a Ifunctioning ' gallbladder. Sixteen patients had normal HIDA scans with gallbladder visualization, and subsequently all were shown by cholecystography (n = IS) or operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A modification of this system was suggested by Imrie et a18 (Table 1) and has been used widely in the United KingdomW l" while some have preferred diagnostic peritoneal lavage for prognostic purposes. 10 This study reappraises the discriminatory value of individual factors determined within 48 hours of admission, assesses the ability of the scoring Eight of the factors considered showed significant differences between the severe and mild outcome groups (Table 3). Each of these eight factors was useful in selecting patients at increased risk of severe disease using the defined cut points (Table 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A modification of this system was suggested by Imrie et a18 (Table 1) and has been used widely in the United KingdomW l" while some have preferred diagnostic peritoneal lavage for prognostic purposes. 10 This study reappraises the discriminatory value of individual factors determined within 48 hours of admission, assesses the ability of the scoring Eight of the factors considered showed significant differences between the severe and mild outcome groups (Table 3). Each of these eight factors was useful in selecting patients at increased risk of severe disease using the defined cut points (Table 4).…”
mentioning
confidence: 99%
“…diagnostic peritoneal lavage for prognostic purposes. 10 This study reappraises the discriminatory value of individual factors determined within 48 hours of admission, assesses the ability of the scoring system of Imrie et at8 to define patients with severe disease, and evaluates modifications to simplify the system but improve its accuracy. …”
mentioning
confidence: 99%
“…Unfortunately, this impressive result was not substantiated in two subse quent studies which reported accuracies of only 38% [8] and 53% [20]. However, the scanning time in these stud ies has varied between 1 h [22] and 6 h [20] with a posi tive test being defined as an absent GB image. Serafini et al [21], in a study of 60 patients with acute pancreatitis, recorded images up to 24 h and classified scans into 5 groups on the basis of the rate of uptake of isotope by the GB and its excretion into the duodenum.…”
Section: Discussionmentioning
confidence: 93%
“…Glazer et al [22] first reported the use of biliary scan ning in acute pancreatitis and diagnosed gallstone pancre atitis with an accuracy of 100%. Unfortunately, this impressive result was not substantiated in two subse quent studies which reported accuracies of only 38% [8] and 53% [20].…”
Section: Discussionmentioning
confidence: 99%
“…A modification of this system was sug gested by Imrie et al [49], which found a positive response in centers with a predominance of AP of biliary etiology [50,51 ]. Many slight modifications of these scor ing systems have been published afterwards with the intention of optimizing their usefulness [52][53][54].…”
Section: Scoring Systemsmentioning
confidence: 99%